PENGAMATAN JENIS-JENIS GULMA PADA TANAMAN SINGKONG (Manihot Esculenta Crantz) DI KELURAHAN DOBONSOLO DISTRIK SENTANI - Lawalata, Jacob Julius (Jurnal Pertanian Terpadu Santo Thomas Aquinas, 2022)
The fluctuating production of cassava plants both nationally and regionally, especially in the province of Papua and Jayapura district, is suspected to be due to the presence of weeds in the cassava plantation area. The presence of weeds in cassava plantations can inhibit growth and even reduce cassava production by 75% if the weeds are not controlled, especially at the beginning of their growth. The type, nature and population of weeds in the cassava plant area will affect the small amount of losses incurred. The presence of these weeds and their impact on cassava plants can be analyzed from the density level, dominance index and species diversity. The purpose of this study was to determine the types of weeds in cassava plantations and the level of density and dominance of each of these weeds. This research was conducted in Dobonsolo Village, Sentani District, Jayapura Regency, from November 2020 to December 2020. The method used in this study was a free survey with the vegetation analysis method using the quadratic method, namely the analysis method by taking data from each plot. example of a quadrant with an area that is calculated in quadrant units (m²). The quadrant used in this study is a square with a size of 2 m x 2 m. The results of observations of weed types found in cassava gardens in Dobonsolo Village, Sentani District, found 15 types of weeds consisting of 9 families, namely Piperaceae, Commelinaceae, Dennstaedtiaceae, Lamiaceae, Euphorbiaceae, Poaceae, Onagraceae, Rubiaceae, and Fabaceae. The dominant type of weed in cassava gardens in Dobonsolo Village, Sentani District, is Peperomia pellucida L from the Piperaceae family with a NJD value of 12.6%.